Analysis of Light Pollution of the Night Sky in Toruń (Poland) - Karpińska, Dominika (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Light pollution is one of the types of environmental pollution. The sky illuminated by the excessive light emission is an inherent element of the modern world. This phenomenon has been known for over a century, but research has been carried out only for several decades. Analysis of the brightness of the sky was made for Toruń (Poland) and neighboring areas.
Keywords: light pollution; light emission; SQM; Toruń; Poland; land cover; zanieczyszczenie światłem; emisja światła; analiza jasności nieba; Polska